2016
DOI: 10.1017/s0030605316000399
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Endangered red panda Ailurus fulgens fulgens to anthropogenic disturbances, and its distribution in Phrumsengla National Park, Bhutan

Abstract: Across much of Asia protected areas have a dual objective of conserving biodiversity and supporting rural and indigenous livelihoods. For the red panda Ailurus fulgens and other sensitive species of concern, even limited anthropogenic disturbance may influence their use of protected areas. We quantified the prevalence of timber collection and livestock grazing, and their impacts on red panda habitat use, in Phrumsengla National Park, Bhutan. Red pandas used sites with at least 20% bamboo cover, as evidenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 13 publications
(28 reference statements)
4
29
1
Order By: Relevance
“…While in another separate study in the PNP, red pandas were recorded in CBL and MCF between 2,860 and 3,597 m (Dendup et al, 2016). In the present study, red panda habitat use was significantly associated with fir forests.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…While in another separate study in the PNP, red pandas were recorded in CBL and MCF between 2,860 and 3,597 m (Dendup et al, 2016). In the present study, red panda habitat use was significantly associated with fir forests.…”
Section: Discussionsupporting
confidence: 42%
“…(1 × 1 m) were superimposed on the center of each understorey quadrat (Dendup et al, 2016). Vegetation data were recorded following Schemnitz (1980) and Dendup et al (2016, Table 1).…”
Section: Field Survey Designmentioning
confidence: 99%
“…Being bamboo specialists, more than 80% of their diet consists of bamboo grass [2932,54]. Previous studies in this region also have shown strong associations between red panda presence and habitats with understorey cover dominated by bamboo grass [26,53]. Red pandas occur in temperate forests ranging from deciduous broad leaved forests to conifer forests.…”
Section: Discussionmentioning
confidence: 99%
“…Although the red panda is protected by international conventions (CITES, 2017) and national law in Nepal (GoN, 1973), its population has continued to decline over the past 30 years (Glatston et al, 2015). The anthropogenic impact on red panda habitat has been identified as a major threat to the conservation of this species in its current distribution range (Acharya et al, 2018;Dendup, Cheng, Lham, & Tenzin, 2017;Dorji, Rajaratnam, & Vernes, 2012;Panthi, Khanal, Acharya, Aryal, & Srivathsa, 2017). A large number of cattle, herders, and their guard dogs have also been responsible for disturbance to red pandas and their habitats (Yonzon & Hunter, 1991a).…”
mentioning
confidence: 99%